2013
DOI: 10.1242/dev.095307
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Bmp10 acts through endothelial Alk1 to mediate flow-dependent arterial quiescence

Abstract: SUMMARYBlood flow plays crucial roles in vascular development, remodeling and homeostasis, but the molecular pathways required for transducing flow signals are not well understood. In zebrafish embryos, arterial expression of activin receptor-like kinase 1 (alk1), which encodes a TGFβ family type I receptor, is dependent on blood flow, and loss of alk1 mimics lack of blood flow in terms of dysregulation of a subset of flow-responsive arterial genes and increased arterial endothelial cell number. These data sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
114
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(119 citation statements)
references
References 55 publications
(76 reference statements)
5
114
0
Order By: Relevance
“…Because our previous data demonstrated that lack of blood flow mimics lack of alk1 with respect to changes in arterial endothelial cell number and gene expression (Corti et al, 2011;Laux et al, 2013), we also performed photoconversion experiments in tnnt2a morphants, which lack heartbeat and blood flow (Sehnert et al, 2002). In the absence of blood flow, we documented decreased proximal displacement and increased distal displacement of alk1-positive endothelial cells between 24 and 48 hpf, compared with controls and alk1 morphants (Fig.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…Because our previous data demonstrated that lack of blood flow mimics lack of alk1 with respect to changes in arterial endothelial cell number and gene expression (Corti et al, 2011;Laux et al, 2013), we also performed photoconversion experiments in tnnt2a morphants, which lack heartbeat and blood flow (Sehnert et al, 2002). In the absence of blood flow, we documented decreased proximal displacement and increased distal displacement of alk1-positive endothelial cells between 24 and 48 hpf, compared with controls and alk1 morphants (Fig.…”
Section: Resultsmentioning
confidence: 83%
“…Arterial endothelial cells that contribute to the contiguous AA1, ICA and CaDI derive from both of these clusters and become alk1 positive only after the onset of blood flow (Corti et al, 2011). We previously reported an increase in caliber of and endothelial cell number in the CaDI in 36 hpf alk1 morphant embryos compared with control siblings (Laux et al, 2013). To define the time course of these changes and to determine whether other alk1-positive arteries behave in a similar manner, we assessed morphology of and counted endothelial cells in proximal (AA1 and ICA; Fig.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Multiple zebrafish BMP homologs, including BMP2b, BMP3, BMP4 and BMP10l, are known to have expression in the myocardium (Chin et al, 1997;Wang et al, 2007;Schoenebeck et al, 2012;Laux et al, 2013). It is likely that two or more homologs may function redundantly during endocardial differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Zebrafish alk1 mutants develop AVMs at a predictable time (approximately 40 h post-fertilization, hpf ) in a predictable location (beneath the midbrain or hindbrain) and therefore serve as a relevant, accessible model for exploring the cellular basis of HHT-associated AVM development (Corti et al, 2011;Laux et al, 2013;Roman et al, 2002).…”
Section: Introductionmentioning
confidence: 99%